Description of Procedural Fluency and Productive Mathematical Disposition of Middle School Students - Darwani, Darwani; Abidin, Zainal; Hardisa, Rahmayuni (Al-Khawarizmi, 2023)
The objectives of this study to describe the level of procedural mathematical fluency of students in solving problems on number pattern material and to describe the level of students' mathematical productive disposition in class VIII SMP Negeri 1 Baitussalam. This study used descriptive qualitative research with three students as subjects grouped into three categories namely high, medium and low. The results showed that mathematical procedural fluency (1) students in the high level category fulfilled all indicators. (2) students in the moderate level category fulfill two of the three indicators. (3) students in the low level category only meet one indicator. And the results for mathematical productive dispositions: (1) students with a high level fulfill all indicators (2) students in the medium level category fulfill five of the seven indicators (3) students in the low level category only fulfill two of the seven indicators.